2012
DOI: 10.1002/bjs.8702
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of outcomes following pathological complete response to neoadjuvant chemoradiotherapy for rectal cancer

Abstract: Background: Following neoadjuvant chemoradiotherapy (CRT) and interval proctectomy, 15-20 per cent of patients are found to have a pathological complete response (pCR) to combined multimodal therapy, but controversy persists about whether this yields a survival benefit. This systematic review evaluated current evidence regarding long-term oncological outcomes in patients found to have a pCR to neoadjuvant CRT. Results: A total of 724 studies were identified for screening. After applying inclusion and exclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
369
5
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 551 publications
(399 citation statements)
references
References 60 publications
(85 reference statements)
14
369
5
11
Order By: Relevance
“…Meta analysis of 12 larger studies worldwide reports 90.2% 5-year survival rate in pCR patients (p = 0.0001) 15 ; similar percentage (90% or more) is mentioned in various other studies 2,4,16 , while others failed to prove relation between pCR and better survival. 15 In the literature, strong evidence exists that patients with pCR have very few local recurrences (2-5% in 5 years) and that there are statistically significant differences, if groups of patients with pCR are compared to those who failed to respond to preoperative treatment. 4,16 It is important to state that in some no local recurrences at all were found in groups of pCR patients.…”
Section: Discussionmentioning
confidence: 73%
“…Meta analysis of 12 larger studies worldwide reports 90.2% 5-year survival rate in pCR patients (p = 0.0001) 15 ; similar percentage (90% or more) is mentioned in various other studies 2,4,16 , while others failed to prove relation between pCR and better survival. 15 In the literature, strong evidence exists that patients with pCR have very few local recurrences (2-5% in 5 years) and that there are statistically significant differences, if groups of patients with pCR are compared to those who failed to respond to preoperative treatment. 4,16 It is important to state that in some no local recurrences at all were found in groups of pCR patients.…”
Section: Discussionmentioning
confidence: 73%
“…With LE, mesorectal lymph nodes are not excised, and lymph node status is correlated with prognosis. A systemic review [43] reported that between 2% to 27% of patients with ypT0 have positive nodes on final pathology. In addition, while LE generally tolerated well with low complication rates, the addition of nCRT prior to LE increases complication rates in current studies.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13]15,20,21 In general, the margin-free resection rate or 6-month progression-free survival is used as an effective surrogate marker of NACRT efficacy in PDA. The pathological response rate is also gaining recognition as an important surrogate.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 For several different types of carcinoma, in some organs, pathological complete response (pCR) to neoadjuvant therapy is correlated with a lower frequency of local recurrence and better survival. [10][11][12][13][14][15] However, very few studies have analyzed the clinicopathological significance of pCR in patients with PDA who received neoadjuvant therapy. 9,16,17 Here we report two cases of pCR to NACRT in PDA, including detailed pathological findings of resected tissues.…”
Section: Introductionmentioning
confidence: 99%